2009
DOI: 10.1038/ijo.2009.162
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a soluble activin type IIB receptor on obesity and insulin sensitivity

Abstract: Myostatin, also known as Growth and Differentiation Factor 8, is a secreted protein that inhibits muscle growth. Disruption of myostatin signaling increases muscle mass and decreases glucose, but it is unclear whether these changes are related. We treated mice on chow and high-fat diets with a soluble activin receptor type IIB (ActRIIB.Fc) which is a putative endogenous signaling receptor for myostatin and other ligands of the TGF-β superfamily. After 4 weeks, RAP-031 increased lean and muscle mass, grip stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
116
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 39 publications
17
116
2
Order By: Relevance
“…In the present study, treatment of mice with sActRIIB (5 mg/kg, three times per week) concurrent with 12 weeks of high-fat feeding prevented the significant increases in body weight, WAT depot weights and circulating triacylglycerols observed in mice receiving vehicle. These data corroborate those of Akpan et al from a study in which high-fat fed mice receiving sActRIIB for 10 weeks also gained less fat mass and had lower glucose and cholesterol concentrations compared with vehicletreated mice [17]. Zhang and colleagues also observed that administration of sActRIIB prevented the significant downregulation of key genes of uncoupling and oxidative metabolism in WAT that was observed in vehicle-treated mice in response to high-fat feeding.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, treatment of mice with sActRIIB (5 mg/kg, three times per week) concurrent with 12 weeks of high-fat feeding prevented the significant increases in body weight, WAT depot weights and circulating triacylglycerols observed in mice receiving vehicle. These data corroborate those of Akpan et al from a study in which high-fat fed mice receiving sActRIIB for 10 weeks also gained less fat mass and had lower glucose and cholesterol concentrations compared with vehicletreated mice [17]. Zhang and colleagues also observed that administration of sActRIIB prevented the significant downregulation of key genes of uncoupling and oxidative metabolism in WAT that was observed in vehicle-treated mice in response to high-fat feeding.…”
supporting
confidence: 88%
“…For instance, mice homozygous for a mutation in the myostatin gene are resistant to diet-induced hepatic steatosis, elevations in inflammatory cytokines and macrophage infiltration/activation in adipose tissue and skeletal muscle compared with wild-type and heterozygous mice [21]. Postnatal blockade of myostatin with a neutralising antibody in obese insulin-resistant mice significantly improved glucose homeostasis, lowered circulating triacylglycerols and increased circulating concentrations of the adipose tissue-derived cytokine, adiponectin [17,22]. The absence of myostatin also appears to protect high-fatfed LDL receptor-null mice from dyslipidaemia and atherogenesis, as LDL receptor/myostatin double knockout mice have decreased VLDL generation, improved lipid profiles and reduced atherogenesis progression [23].…”
mentioning
confidence: 99%
“…Furthermore, on the basis of recent findings, blockade of activin type II receptors via an antibody approach may also represent a novel therapeutic modality to aid in switching the metabolic balance between adiposity and muscularity, since an increase in skeletal muscle mass via inhibition of the myostatin pathway was accompanied by a decrease in white adipose tissue in mice on a normal or high-fat diet (55). One recently identified mechanism helping to explain this effect is that an ActRIIB antibody has been shown to induce a functional increase in brown fat (56), resulting in enhanced heat production by actually increasing the lipid content in the brown fat tissue (56).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Researchers from our laboratory, and others, have reported improvements in muscle mass and function in wild-type mice in the dystrophic-phenotype mdx mice, using both an antibody directed against MSTN and the MSTN propeptide. 21,22,30 The sActRIIB molecule has recently been shown to improve muscle function in a mouse model of amyotrophic lateral sclerosis, 50 increase muscle mass and reduce adiposity in mice fed a high-fat diet, 51 and attenuate muscle dysfunction in wild-type mice exposed to normobaric hypoxia. 52 The therapeutic efficacy of sActRIIB observed during hypoxic exposure is especially pertinent to DMD pathology, because respiratory impairments in patients result in the need for ventilatory assistance at a young age.…”
Section: Discussionmentioning
confidence: 99%